Does PSM matter among innovative government managers? (REGE Revista de Gestão, 2020)
Purpose – The need to improve the efficiency and quality of public services has increased the interest in innovation. This study seeks to understand the relationship between the Public Service Motivation (PSM) index and the profile of strategic-level public servants who are considered innovative. Design/methodolog/approach – Questionnaires were applied to the group of government managers who registered their projects in an innovation competition. Data were analyzed using t-test, multiple correspondence analysis (MCA) and hierarchical cluster analysis (HCA). Findings – This paper concluded that the PSM level of these innovative public servants is significantly greater than public servants overall. In terms of the profile of these innovative government managers, it was found that the majority were female, with a high level of education and a background in Information Technology. Practical implications – The discovery that innovative government managers have a significantly higher PSM (p < 0.05) than public servants overall may be relevant, because it confirms a statistical tendency that it would be advantageous for policy-makers to invest in actions that increase public servant PSM since these servants with high PSM are more innovative. Originality/value – This article has sought to fill a gap in studies that associate the level of PSM with the innovation practices in the public sector, as well as verify the profile of public servants with high levels of motivation in public service (PSM).